The Sharia Banking Dispute Settlement Forum as the Principle of Freedom of Contract Post Decision of the Constitutional Court No. 93/PUU-X/2012 - Nurzahiroh, Khamidah; Putri, Edelweiss (LifeSciFi, 2023)
The resolution of disputes in Islamic banking saw significant changes through the judicial review of Article 55 of Law no. 21 of 2008 in Indonesia. Before this review, Islamic banking disputes were typically handled in courts based on the contract terms. Article 55, paragraph (2), allowed parties to settle disputes in accordance with the contents of the contract using alternative methods, creating confusion. Some banks chose district courts instead of religious courts, which had exclusive jurisdiction. This interpretation, extending freedom of contract to forum selection, created ambiguity. Constitutional court decision No. 93/PUU-X/2012 aimed to clarify matters and reinforced religious courts’ authority in Sharia banking dispute resolution. However, the principle of freedom of contract still plays a role in forum selection, albeit with limitations. This raises two key questions: First, does Constitutional Court Decision No. 93/PUU-X/2012 align with the principle of freedom of contract? Second, what are the legal consequences regarding Islamic banking dispute resolution? According to the judicial review, religious courts now unequivocally have the authority to resolve sharia banking disputes. Any agreement to settle disputes in general courts is considered null and void as it contradicts existing laws and regulations.